CLINICAL COURSE OF CONGENITAL PNEUMONIA IN NEONATES AND THE DIAGNOSTIC SIGNIFICANCE OF INFLAMMATORY MARKERS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Background: Congenital pneumonia remains a significant cause of morbidity and mortality in neonates worldwide. Early detection is often challenging due to nonspecific clinical symptoms, making the identification of reliable inflammatory markers crucial for timely diagnosis and management. This study aims to investigate the clinical course of congenital pneumonia in neonates and to evaluate the diagnostic value of specific inflammatory markers in predicting disease severity and progression. A prospective observational study was conducted in neonates diagnosed with congenital pneumonia.